PENERAPAN METODE DRILL DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN SISWA KELAS II SD - Naila Restu Kurnia; Siti Ruqoyyah; Uke Viani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was triggered by the low level of the learning outcomes in mathematics learning at primary schools. It was also based on the results of observation finding that there were problems constraining the success of learning mathematics at primary schools. One of which was the students’ low achievement and mathematics learning which were less attractive to students. This research aimed to improve the students’ mathematics learning outcomes on multiplication material by implementing the drill method. This research was classroom action research in which the researchers compared the increase of students’ learning outcomes before and after the implementation of the drill method in two cycles. This research was conducted in SDN Cibeber 1 at Kecamatan Cimahi Selatan, Kota Cimahi. The results of this study indicated that the students’ mathematics learning outcomes on multiplication material increased as much as 52.2% after the implementation of the drill method. Thus, it could be concluded that the drill method could increase the mathematics learning outcomes of grade II elementary students in the multiplication material.